The correlations between parental warmth and children’s approaches to learning: a moderated mediation model of self-efficacy and teacher-child closeness - Liu, Yongli; Wang, Wei; Wei, Sumei; Wang, Pengcheng; Chen, Kun; Liu, Jing; Chen, Junjun (Frontiers in Psychology, 2024)
Researchers have increasingly considered approaches to learning (ATL) a key indicator of school readiness. Our study purposed to examine the impacts of parental warmth on children's approaches to learning, and the mediating role of self-efficacy, as well as the moderating role of teacher-child closeness in this relationship. Using a whole-group sampling method, 414 Chinese children aged 5-6 years participated this research together with their parents and teachers. Parents of those children were asked to fill out in person questionnaires on parental warmth, children's approaches to learning, and self-efficacy. Children's teachers completed the questionnaire regarding teacher-child closeness. Results indicated that children with high parental warmth were more likely to get high approaches to learning and their self-efficacy played a partial mediating role in this link.In addition, teacher-child closeness moderated the correlation between parental warmth and children's self-efficacy. Specifically, the association between parental warmth and children's self-efficacy was stronger for children with high teacher-child closeness than those with low teacher-child closeness. The results extend our understanding of how parental warmth affects children's approaches to learning, revealing that strategies that could enhance self-efficacy would be effective in improving children's approaches to learning.